Access to Care in the Wake of Hurricane Sandy, New Jersey, 2012. (13th May 2016) - Davidow, Amy L.; Thomas, Pauline; Kim, Soyeon; Passannante, Marian; Tsai, Stella; Tan, Christina
Abstract: Objective: Evacuation and damage following a widespread natural disaster may affect short-term access to medical care. We estimated medical care needs in New Jersey following Hurricane Sandy in 2012. Methods: Hurricane Sandy-related questions regarding medical needs included in the Behavioral Risk Factor Surveillance System survey were administered to survey respondents living in New Jersey when Sandy occurred. Results: Recently arrived foreign-born residents were more likely than US-born residents to need medical care following Sandy. Others with greater medical needs included the uninsured and evacuees. Persons who evacuated or lived in areas that experienced the greatest hurricane impact were less likely to be able to fill a prescription. Only 15% of New Jerseyans were aware of the Emergency Pharmaceutical Assistance Program (EPAP), a federal program which allows prescription refills for the uninsured following a disaster. Recently arrived foreign-born residents and the uninsured were less frequently aware of EPAP: 8.7% and 10.9%. Conclusions: Populations with impaired access to care in normal times—such as the recently arrived foreign-born and the uninsured—were also at risk of compromised access in the hurricane's aftermath. Measures to address prescription refills during a disaster need better promotion among at-risk populations. ( Disaster Med Public Health Preparedness . 2016;10:485–491)